2020
DOI: 10.1007/978-3-030-61244-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Personal Health Records to Support Emergency Services

Abstract: Smart City systems capture and exchange information with the aim to improve public services. Particularly, healthcare data could help emergency services to plan resources and make life-saving decisions. However, the delivery of healthcare information to emergency bodies must be balanced against the concerns related to citizens' privacy. Besides, emergency services face challenges in interpreting this data; the heterogeneity of sources and a large amount of information available represent a significant barrier.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The current global, socio-economic impact and burden of either conflict-related or environmental catastrophes have regained accelerated research attention due to recent geopolitical events and climate change. [1][2][3][4][5][6] Many have suggested that the use of personal health records could support an effective understanding of both acute and chronic diseases associated with these catastrophes that present a cross-border challenge to the medical community. 2 3 5 6 However, the economic impact of PHR designs for multi-user co-ownership is yet to be fully understood and modelled.…”
Section: Rationale Gpoc Economic Modelsmentioning
confidence: 99%
“…The current global, socio-economic impact and burden of either conflict-related or environmental catastrophes have regained accelerated research attention due to recent geopolitical events and climate change. [1][2][3][4][5][6] Many have suggested that the use of personal health records could support an effective understanding of both acute and chronic diseases associated with these catastrophes that present a cross-border challenge to the medical community. 2 3 5 6 However, the economic impact of PHR designs for multi-user co-ownership is yet to be fully understood and modelled.…”
Section: Rationale Gpoc Economic Modelsmentioning
confidence: 99%
“…In the Smart City environment, data is gathered by different means and from different sources to improve city services. In recent years, attention has focused on using Electronic Health Records to assist emergency services [1,8,7].…”
Section: Background and Related Workmentioning
confidence: 99%
“…This information could provide a snapshot of people's health status. For instance, identifying vulnerable people or people otherwise requiring special assistance in the context of an emergency [7,8]. However, assessing ongoing health issues represents a challenge to first responders.…”
Section: Introductionmentioning
confidence: 99%
“…From the other side, many recent studies about EHR are becoming more specific with concentration on deep issues linked to answer questions like how to exploit EHR capabilities in analytics, prediction and managing diseases, epidemics, and pandemics [19]. Other studies stepped farther by investigating issues of integrating different EHR systems, data validation and data exchange with other information systems [20][21][22]. The outcomes of these studies have become more essential and attractive to all stakeholders in healthcare with COVID-19 pandemic outbreak [23][24][25].…”
Section: Introductionmentioning
confidence: 99%